GROWTH THRESHOLD AND DEGREE DAYS REQUIREMENT FOR DEVELOPMENT AND GROWTH OF CITRUS MEALYBUG Planococcus citri (Risso), HEMIPTERA : PSEUDOCOCCIDAE - & Al-Zubaidy, Al-Shammari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Laboratory studies was conducted in Biocontrol unit- Faculty of Agriculture- University of Baghdad in order to determine the impact of different temperatures  15,  20,  25, 30 and 35 ±2 C°  on the development and growth rate of  different stages of mealy bug P.citri. The results showed that the total developmental time from (egg - adult)of the mealy bug were  24.0, 28.08, 39.67 and 73.31 days  respectively. With significant rearing differences on temperatures 15, 20, 25 and 30 ±2  C°  respectively, while no development and growth rate on temperature  35±C°. the developmental threshold for the mealy bug stages  eggs,  crawlers, 2nd  and 3rd nymphal instars as well as the duration of the egg to adult were different, being 7.1, 7.26, 7.08, 7.12 and 7.15C° respectively, while 116.27, 136.98 and 172.4 thermal units for  degree days required for growth and development while the thermal constant for the period from egg to adult was 526.31. Optimum temperature was 27.85C ͦ  while Upper threshold was 33.64 C° for P.citri  Which refers to the lack of suitable high temperature for growth and development .